Moslem Women in Paris on Novel of Tahar Ben Jelloun: Les Yeux Baissés - Syamsudin, Oom Rohmah; Madinier, Rémy (Makassar State University, 2023)
Abstract. This article aims to describe the cultural conflicts occurred by Maghreb immigrants in Paris, especially female immigrants who have various conflicts, due to the difference perception of women both in Maghreb and in France. As a qualitative research, this research instrument is the researchers themselves with data from the novel Les Yeux Baissés by Tahar Ben Jelloun, a Maghreb author living in Paris. The data were then analyzed using the Semiotic theory of Roland Barthes: the novel is considered as a sign to be interpreted. The results of the study indicate that the cause of the conflicts is the differences in tradition, race, and religion. These differences make them feel “unaccepted” in France. Therefore, Moslem women in Paris have two types of cultural identities: Identity of being (the mother of Fathma, the main character) and Identity of becoming (Fathma, the main character). Besides, these Maghebian immigrants belong to the diaspora’s group: First, the Essentialists, diaspora who closed themselves off, just carried on their traditions, culture and religion as they did back home. Second, whom adopt the French culture, religion, and way of life. Third, those with 'floating' traits: born in France, do not know the cultural traditions of their hometown, only know French culture which “does not accept them”. Therefore it can be said that the ‘floating’ generation needs a 'special place' that is neither the culture of their parents, nor the culture of France, and that third place can be called a 'place of transit'.Keywords: Maghreb Diaspora, Moslem Women, Cultural Conflict, Place of Transit